Association Study Between Methylation in the Promoter Regions of cGAS, MAVS, and TRAF3 Genes and the Risk of Cervical Precancerous Lesions and Cervical Cancer in a Southern Chinese Population - Huang, Shiqi; Li, Ruixin; Huang, Xiuxia; Zheng, Shaoling; Wang, Lijun; Wen, Zihao; Zou, Xiaoqian; Wu, Jing; Liu, Yumei; Liu, Dandan; Wang, Yao; Dong, Shirui; et al. (Frontiers in Genetics, 2019)
A case-control study was used to explore the association between the methylation status in the promoter regions of the cGAS, MAVS, and TRAF3 genes and the diseases of cervical precancerous lesions (CPL) and cervical cancer (CC) in a Southern Chinese population, and to further explore their interaction effects with high-risk HPV (hrHPV) infection and environmental factors in these diseases. The study protocol was approved by the ethics committee of The First Affiliated Hospital of Jinan University, and this study was performed in 97 healthy controls, 75 patients with CPL and 33 patients with CC, while each participant has read and signed the informed consent forms before enrolment. The promoter methylation status genes were detected from the bisulfite-treated DNA by the bisulfite sequencing PCR (BSP) technique, which was carried out using MethPrimer. The cGAS, MAVS, and TRAF3 promoter methylation levels in CPL (CPLcGAS= 35.40%, CPLMAVS= 24.26%, and CPLTRAF3= 96.76%) were significantly higher than those in the control (ControlcGAS= 31.87%, ControlMAVS= 21.16%, and ControlTRAF3 = 96.26%, PcGAS< 0.001, PMAVS< 0.001, and PTRAF3 = 0.001); however, there was no significant differences between the CC and control. In the logistic regression model with adjusted covariants, compared with the individuals whose cGAS methylation levels were less than or equal to 31.87%, the women with the levels more than 31.87% increased the risk of CPL by 2.49 times (ORa = 2.49, 95% CI = 1.31-4.75, Pa = 0.006). The women with MAVS methylation levels above 21.16% were 1.97 times more likely to have CPL than the those with the levels less than 21.16% (ORa = 1.97, 95% CI = 1.06-3.69, Pa = 0.033). A synergistic interaction was found between hrHPV and gene promoter methylation levels of cGAS and MAVS in CPL; however, no potential interaction was observed in CC. The promoter methylation levels in cGAS, MAVS, and TRAF3 genes are higher in CPL than in control, indicating that hypermethylation might be an early event in the progression of cervix neoplasia. The interaction between the promoter methylation levels in cGAS and MAVS genes and hrHPV infection might play a role in the development of CPL.